Narrow‐Bandgap Single‐Component Polymer Solar Cells with Approaching 9% Efficiency. Issue 32 (27th June 2021) - Li, Siying; Yuan, Xin; Zhang, Qilin; Li, Bin; Li, Yuxiang; Sun, Jianguo; Feng, Yifeng; Zhang, Xuning; Wu, Ziang; Wei, Huan; Wang, Mei; Hu, Yuanyuan; et al.
Abstract: Two narrow‐bandgap block conjugated polymers with a (D1–A1)–(D2–A2) backbone architecture, namely PBDB‐T‐ b ‐PIDIC2T and PBDB‐T‐ b ‐PTY6, are designed and synthesized for single‐component organic solar cells (SCOSCs). Both polymers contain same donor polymer, PBDB‐T, but different polymerized nonfullerene molecule acceptors. Compared to all previously reported materials for SCOSCs, PBDB‐T‐ b ‐PIDIC2T and PBDB‐T‐ b ‐PTY6 exhibit narrower bandgap for better light harvesting. When incorporated into SCOSCs, the short‐circuit current density ( J sc ) is significantly improved to over 15 mA cm −2, together with a record‐high power conversion efficiency (PCE) of 8.64%. Moreover, these block copolymers exhibit low energy loss due to high charge transfer (CT) states ( E ct ) plus small non‐radiative loss (0.26 eV), and improved stability under both ambient condition and continuous 80 °C thermal stresses for over 1000 h. Determination of the charge carrier dynamics and film morphology in these SCOSCs reveals increased carrier recombination, relative to binary bulk‐heterojunction devices, which is mainly due to reduced ordering of both donor and acceptor fragments. The close structural relationship between block polymers and their binary counterparts also provides an excellent framework to explore further molecular features that impact the photovoltaic performance and boost the state‐of‐the‐art efficiency of SCOSCs. Abstract : Two narrow‐bandgap block copolymers PBDB‐T‐ b ‐PIDIC2T and PBDB‐T‐ b ‐PTY6 are designed and synthesized for single‐component polymer solar cells, and a record‐high efficiency of 8.64% is obtained. Moreover, these block copolymers exhibit relatively small energy loss and improved storage stability under both ambient condition and continued 80 °C thermal stresses for over 1000 h.